Efficient rejection of organic compounds using functionalized ZSM-5 incorporated PPSU mixed matrix membrane. Issue 25 (9th March 2017) - Saranya, R.; Arthanareeswaran, G.; Ismail, A. F.; Reddy, N. Lakshmana; Shankar, M. V.; Kweon, Jihyang
Abstract : Zeolite (ZSM-5) and functionalised zeolite blended polyphenylsulfone (PPSU) mixed matrix membranes (MMMs) were fabricated for comparing their performance with virgin PPSU. Abstract : Zeolite (ZSM-5) and functionalised zeolite blended polyphenylsulfone (PPSU) mixed matrix membranes (MMMs) were fabricated for comparing their performance with virgin PPSU. Similar to zeolite-MMMs, functionalised zeolites such as Fe-ZSM-5 (Fe-Z) and Cu-ZSM-5 (Cu-Z) were mixed with PPSU in the presence of N -methyl pyrrolidone (NMP) solvent. The synthesized zeolite nanoparticles were ultra-sonicated before incorporation to ensure uniform dispersion in PPSU. The PPSU MMMs with incorporated nanomaterials were fabricated as flat sheet modules by means of the phase inversion method. The developed MMMs were examined for homogeneity and characterized for their properties, such as surface hydrophilicity, membrane morphology, thermal stability and surface roughness. An enhanced pure water flux of 62 L m −2 h −1 and a highest lignin retention of 85.2% were observed for a PPSU membrane with 0.5 wt% of zeolite nanomaterials incorporated. The 3D porous structure of the zeolite favoured the enhancement of flux during water and lignin separation. However, the incorporation of functionalised zeolite nanomaterials influenced the increase in maximum lignin rejection to 88.5%. The performance and anti-fouling ability of synthesized MMMs has been evaluated based on the rejection of organic components. Higher preferential permeation with great rejection of lignin were simultaneously observed for zeolite and Cu–zeolite incorporated MMMs.